2016
DOI: 10.1186/s12884-016-0878-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pro-breastfeeding intervention on the maintenance of breastfeeding for 2 years or more: randomized clinical trial with adolescent mothers and grandmothers

Abstract: BackgroundBeing an adolescent mother and cohabiting with the maternal grandmother have been shown to be risk factors for a shorter breastfeeding duration. The objective of this study was to assess whether the positive effects of a pro-breastfeeding intervention aimed at adolescent mothers and maternal grandmothers on the prevalence of breastfeeding observed in the first year of life were maintained at 2 years of age.MethodsThis study is the continuation of a randomized clinical trial initiated in 2006 involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
4
0
8
Order By: Relevance
“…A study conducted in Porto Alegre (RS) demonstrated an increased prevalence of breastfeeding in the first year of life, especially when the mothers did not live with their own mothers, that is, with their child’s maternal grandmother. ( 12 ) This result is similar to that of a research carried out in the United Kingdom where, in general, the mothers with frequent contact with their mothers and mothers-in-law were associated with lower rates of breastfeeding initiation and a shorter duration of it. However, cohabitation of the mother with her mother-in-law did not fit into this tendency, that is, daily living of the mother with paternal grandmothers was associated with fewer probabilities of early weaning.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted in Porto Alegre (RS) demonstrated an increased prevalence of breastfeeding in the first year of life, especially when the mothers did not live with their own mothers, that is, with their child’s maternal grandmother. ( 12 ) This result is similar to that of a research carried out in the United Kingdom where, in general, the mothers with frequent contact with their mothers and mothers-in-law were associated with lower rates of breastfeeding initiation and a shorter duration of it. However, cohabitation of the mother with her mother-in-law did not fit into this tendency, that is, daily living of the mother with paternal grandmothers was associated with fewer probabilities of early weaning.…”
Section: Discussionsupporting
confidence: 87%
“…In models adjusted for unplanned 120 pregnancy, maternal employment, and head of household employment, not breastfeeding was associated with an increased risk of EPDS≥13 compared with breastfeeding (adjusted OR, 1.52; 95% CI, 1.12 to 2.06). 202 The three studies that found no difference in depression scores and breastfeeding status measured outcomes at a similar time point (4 to 8 weeks postpartum). In one (N=551) unadjusted analyses showed no association between current breastfeeding (at 4 weeks) and EPDS scores ≥13 (7% vs. 9%, respectively; p=0.48).…”
Section: Resultsmentioning
confidence: 99%
“…For the present study, sample size power was calculated a posteriori, considering the sample available for analysis. The following parameters were used: breastfeeding prevalence of 69.7% at 6 months, 50.1% at 12 months, and 32.2% at 24 months [ 12 , 15 ], and a minimum relative risk of 1.25, 1.5, and 1.65, respectively, to assess associations between the variables and outcomes of interest. The sample available for assessing the outcome (breastfeeding) at 6, 12, and 24 months presented a power of at least 80% in the two-tailed hypothesis test, at a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%